2016
DOI: 10.3892/or.2016.5122
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-374, a potential radiosensitizer for carbon ion beam radiotherapy

Abstract: In this study, we compared the microRNA (miRNA) profiles of a control and X-ray- and carbon ion beam-resistant cells to identify miRNAs that can be used as radiosensitizers and biomarkers. Mouse squamous cell carcinoma line NR-S1, its X-ray-resistant derivative X60, and its carbon ion beam‑resistant derivative C30 were subjected to miRNA microarray analysis. Expression of miRNAs shown to be upregulated or downregulated in the microarray analysis was confirmed by qRT-PCR. Downregulated miRNAs were overexpressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…microRNAs (miRs) are vital regulators of many pathological and physiological processes, including metastasis and tumorigenesis [11]. In addition, miR-374 has been suggested to be a novel biomarker for determining the most appropriate treatment for cancer and a novel radiation sensitizer for carbon ion beam radiotherapy [12]. In the present study, we aim to investigate the effects of miR-374 on proliferation, migration, invasion, and apoptosis of human SCC cells by targeting Gadd45a through the P53 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRs) are vital regulators of many pathological and physiological processes, including metastasis and tumorigenesis [11]. In addition, miR-374 has been suggested to be a novel biomarker for determining the most appropriate treatment for cancer and a novel radiation sensitizer for carbon ion beam radiotherapy [12]. In the present study, we aim to investigate the effects of miR-374 on proliferation, migration, invasion, and apoptosis of human SCC cells by targeting Gadd45a through the P53 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, miR‐374b overexpression in BxPC3‐R cells recovered cisplatin sensitivity almost to the levels displaying in BxPC3 parental cells. In the same year, Baek et al first screened the change of miRNAs with microarray analysis in mouse squamous cell carcinoma line NR‐S1, X60 cells (established by irradiating NR‐S1 cells with 10 Gy of X‐ray radiation once every 2 weeks) and C30 cells (established by irradiating NR‐S1 cells with 5 Gy of carbon ion beam radiation once every 2 weeks). They also demonstrated that miR‐374c‐5p and miR‐196a‐5p were down‐regulated.…”
Section: The Role Of Mir‐374 In Tumorigenesismentioning
confidence: 99%
“…The aberrant expression of microRNA‐374 (miR‐374) has been reported in many types of human tumours, including gastric cancer, lung cancer and oesophageal cancer . Furthermore, miR‐374 has been identified as a novel biomarker in determining the most appropriate treatment option for cancer and a novel radiation sensitizer for carbon ion beam radiotherapy . Tyrosinase (TYR) is a copper‐containing enzyme known for its participation in a variety of biological processes including wound healing, pigment production, exoskeleton fabrication and innate immunity and hardening .…”
Section: Introductionmentioning
confidence: 99%